Digitalisation assistance of semprong and simping Small and Medium Enterprises (SME) in Desa Taringgul Tonggoh Wanayasa - Hanifa, Adinda Nur; Rasheefah, Aletha Irshaina; Fatkhurahmah, Isnaeni Fajar (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
Digitalisation is one of the steps in managing Small and Medium enterprises (SMEs) that now needs to be taken as technology develops. Business digitalisation by SMEs in Indonesia is still not implemented and paid enough attention, including by Taringgul Tonggoh Village, Wanayasa District, Purwakarta Regency. This results in several problems for SMEs founders, such as obstruction of product promotion and marketing activities, which can affect the development of SMEs themselves. So, digitalisation assistance is needed for SMEs so they can maximize digitalisation. This service was carried out in Taringgul Tonggoh Village to provide SMEs players with an understanding of the use of digital media in running SMEs. The methods used in this program are socialization, mentoring, and surveys. The results obtained from this program are an increased understanding of online product marketing and social media management for SMEs. This program also updates logos and labels and registers production house locations on Google Maps. Business digitalization can provide great opportunities for SMEs to increase buyer interest.